THE USE OF INSTAGRAM VLOG FOR ENGLISH SPEAKING PRACTICES: STUDENTS’ PERCEPTIONS AT SMAN 13 PALEMBANG - Walia Anggraini; Dian Erlina; Husnai Husnaini (EXPOSE (Journal of English Education and for Specific Purpose), 2023)
The aim of this study was to find out students’ perceptions of Instagram vlog for English speaking practices at SMAN 13 Palembang. The qualitative research method with a case study approach was applied in this study. The participants of this study were four students of XI IPA 4 at SMAN 13 Palembang. The data obtained from interview were analyzed by using thematic analysis. The findings of this research showed that there were some advantages and limitations of Instagram vlog in speaking practices, namely: (1) Improve English students’ Pronunciation, (2) Develop English students’ Vocabulary, (3) Improve English students’ grammar (4) Improve English students’ speaking Fluency, (5) Increase Self-confident English Students’ Speaking, (6) Increase motivation for English students’ Speaking, (7) Problem with Internet connection.